2005
DOI: 10.1074/jbc.m501826200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Core Protein Acts as a trans-Modulating Factor on Internal Translation Initiation of the Viral RNA

Abstract: Translation initiation of hepatitis C virus (HCV) RNA occurs through an internal ribosome entry site (IRES) located at its 5 end. As a positive-stranded virus, HCV uses the genomic RNA template for translation and replication, but the transition between these two processes remains poorly understood. HCV core protein (HCV-C) has been proposed as a good candidate to modulate such a regulation. However, current data are still the subject of controversy in attributing any potential role in HCV translation to the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 61 publications
3
44
0
1
Order By: Relevance
“…A capped RNA encoding Renilla luciferase (RLuc) was used as an internal control to normalize transfection efficiency. The validity of similar systems in addressing IRESdependent translation mechanisms has been shown previously (Boni et al, 2005;Shimoike et al, 1999). Total RNA was extracted from CSFV strain Shimen.…”
Section: Classical Swine Fever Virus (Csfv) Is a Member Of The Genusmentioning
confidence: 87%
“…A capped RNA encoding Renilla luciferase (RLuc) was used as an internal control to normalize transfection efficiency. The validity of similar systems in addressing IRESdependent translation mechanisms has been shown previously (Boni et al, 2005;Shimoike et al, 1999). Total RNA was extracted from CSFV strain Shimen.…”
Section: Classical Swine Fever Virus (Csfv) Is a Member Of The Genusmentioning
confidence: 87%
“…DDX3 is known to interact with the hepatitis C virus (HCV) core protein, [40][41][42] which can differentially modulate the internal ribosome entry site (IRES)-mediated translation of the HCV RNA. 43,44 A recent report shows that overexpression of DDX3, despite its suppressing effect on cap-dependent translation, can activate the initiation of HCV …”
Section: Discussionmentioning
confidence: 99%
“…This result further supported that MAPKAPK3 modulated the HCV protein level but not the intracellular HCV RNA level. Since HCV IRES-mediated translation was specifically modulated by HCV core protein in previous studies (23,24) and knockdown of MAPKAPK3 significantly decreased HCV IRES activity in the presence of core protein in the current study, these data indicated that modulation of HCV IRES-mediated translation by core protein occurred through MAPKAPK3 protein. Moreover, overexpression of mutant core containing the necessary region to bind to MAPKAPK3 competed away the protein interaction between wild-type core and MAPKAPK3, and hence HCV IRES activity was impaired.…”
Section: Discussionmentioning
confidence: 72%
“…These data indicate that MAPKAPK3 is involved in HCV IRES-mediated translation. It has been previously reported that HCV core stimulated HCV IRES activity (23,24). Indeed, overexpression of core protein increased HCV IRES activity 1.5-fold compared to vector control, and core-mediated IRES activity was further elevated by MAPKAPK3 in a dose-dependent manner (Fig.…”
Section: Identification Of Cellular Proteins Interacting With Hcv Cormentioning
confidence: 70%